Conductive laminate, optical device using the same, and method for producing conductive laminate

By stacking the conductive laminates containing tin composite oxide and low-tin content oxide sequentially on the transparent substrate side, the problem of increasing resistance of the conductive laminate in high temperature and high humidity environment is solved, and low resistance and high transmission are achieved The effect of rate is suitable for a variety of optical devices.

CN115210066BActive Publication Date: 2024-12-27DEXERIALS CORP
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202180017242.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-03
Filing Date
2021-02-25
Publication Date
2024-12-27
Estimated Expiration
2041-02-25

AI Technical Summary

Technical Problem

The surface resistance of the existing conductive laminated body has increased dramatically in high temperature and high humidity environments, making it difficult to use for a long time. The use of indium tin composite oxide as a conductive film has problems such as rarity and affecting the human body.

Method used

The first transparent material layer and the silver metal layer are sequentially laminated with a transparent substrate side. The first transparent material layer is composed of a composite metal oxide containing 10% or more than 90% of tin, and the second transparent material layer is composed of zinc and tin content. The metal oxide is composed of less than 10%, and the conductive laminate is formed by sputtering technology.

Benefits of technology

It realizes a conductive laminate that maintains low resistance and high transmittance in high temperature and high humidity environments. It is suitable for power-saving and high-performance optical devices, reducing surface resistance and improving full light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115210066B_ABST
    Figure CN115210066B_ABST
Patent Text Reader

Abstract

The present invention provides a conductive laminate having low resistance and high transmittance for a long time, various optical elements having the same, and a method for manufacturing the conductive laminate. The conductive laminate (1) has a transparent substrate (2) and a first transparent material layer (3), a metal layer (4) having silver as a main component, and a second transparent material layer (5) are sequentially stacked on at least one surface of the transparent substrate (2) from the transparent substrate (2) side. The first transparent material layer (3) is composed of a composite metal oxide containing at least zinc and tin and containing 10 atomic % or more and 90 atomic % or less of tin. The second transparent material layer (5) is composed of a metal oxide containing zinc and having a tin content of 10 atomic % or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present technology relates to conductive laminates used, for example, in touch panels, light-adjusting elements, electrophoretic optical elements, light-emitting elements, antennas, etc. This application claims priority based on Japanese Patent Application No. 2020-035784 filed in Japan on March 3, 2020, which is incorporated herein by reference. Background Art

[0002] Transparent, conductive materials have long been used in various optical devices. Examples include touch panels that are layered on image sensor devices and detect the location of a press through changes in capacitance, dimming elements that utilize electrochromism to electrically and variably adjust the intensity of external light, light-emitting elements that utilize electroluminescence, electrophoretic optical elements that utilize electric fields to manipulate charged particles dispersed in a liquid, and antennas that maintain visibility even when attached to windows.

[0003] The electrodes used in these optical devices are required to be optically transparent and, due to operational challenges, to have improved electrical conductivity. Therefore, transparent materials with low electrical resistance are required. As such, ITO (Indium Tin Oxide), a composite oxide of indium and tin, is widely used. ITO already occupies a large market share. However, to reduce resistance and improve transparency, ITO requires film formation at high temperatures or post-film heat treatment, which presents problems when used on heat-sensitive substrates and components.

[0004] Therefore, the development of materials with low resistance and high transparency when not heated is being promoted, and zinc-based oxides such as Zn-O, In-Zn-O (IZO), Al-Zn-O (AZO), and Sn-Zn-O (ZTO) are being studied as alternatives to ITO. Of these zinc-based oxides, AZO and ZTO are more preferable because they do not contain indium, which has concerns about its potential harmful effects on the human body.

[0005] However, the structure of plasma televisions and other devices releases electromagnetic waves from their screens. Various transparent materials have been developed to absorb these electromagnetic waves. A laminate composed of very thin silver films sandwiched between high-refractive-index transparent materials is known to be very effective, and this has been extensively researched and developed. This laminate uses silver to impart conductivity, and the optical interference effect between the high-refractive-index material and the silver suppresses surface reflection, increasing transmittance. This achieves high transmittance and low electrical resistance. Furthermore, examples of this laminate being used in the aforementioned optical devices and the like have been seen.

[0006] Thus, a transparent conductive film having both permeability and conductivity can be considered for various applications, but in order to achieve power saving and high-speed operation of the above-mentioned elements, further low resistance and high transmittance are required. In metal oxides such as ITO, in order to reduce the resistance value, the thickness of the film needs to be increased. If the thickness of the film is increased, the transmittance will decrease, making it difficult to obtain sufficient characteristics. Therefore, it is believed that a laminate obtained by clamping the two sides of the metal with a transparent material is very beneficial. In particular, in the laminate obtained by clamping the two sides of silver with a composite oxide of tin and zinc as a transparent material as exemplified in Patent Document 2, the composite oxide of tin and zinc is chemically stable and has excellent water vapor barrier properties, so it can suppress the degradation of the silver thin film and obtain stable characteristics.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent No. 4820738

[0010] Patent Document 2: Japanese Patent No. 4961786

[0011] Non-patent literature

[0012] Non-patent document 1: Appl. Phys. A (2014) 116: 1287-1291 Summary of the Invention

[0013] Problems to be solved by the invention

[0014] However, it is known that when a conductive laminate, which is a conductive thin film and is formed by sandwiching silver with a composite oxide of tin and zinc as a transparent material and stored in an accelerated environment of high temperature and high humidity, maintains transmittance performance, its surface resistance increases dramatically, making it difficult to use as a conductive film. This indicates that there are problems with the long-term use of conductive laminates.

[0015] Therefore, a conductive laminate with high transmittance and low resistance even after storage in an accelerated environment of high temperature and high humidity is desired. In addition, the indium tin composite oxide used as a conductive film is rare, and it is desirable not to use indium, which is also worried about its harmful effects on the human body.

[0016] Therefore, the present technology has been made in view of the above-mentioned problems, and an object thereof is to provide a conductive laminate having low resistance and high transmittance for a long period of time, various optical elements including the conductive laminate, and a method for producing the conductive laminate.

[0017] Methods for solving problems

[0018] The present inventors have repeatedly conducted in-depth research to solve the above-mentioned problems. As a result, they have discovered that in a conductive laminate comprising a first transparent material layer, a metal layer mainly composed of silver, and a second transparent material layer stacked in this order from the transparent substrate side, when the first transparent material layer is composed of a composite metal oxide containing at least zinc and tin and a specified amount of tin, and the second transparent material layer is composed of a metal oxide containing zinc and having a tin content of not more than a specified amount, it is possible to achieve both high transmittance and low resistance, thereby completing the present invention.

[0019] That is, the present technology is a conductive laminate, which comprises a first transparent material layer, a metal layer mainly composed of silver, and a second transparent material layer stacked in order from the transparent substrate side on at least one surface of a transparent substrate, wherein the first transparent material layer is composed of a composite metal oxide containing at least zinc and tin and containing 10 atomic % or more and 90 atomic % or less of tin, and the second transparent material layer is composed of a metal oxide containing zinc and having a tin content of 10 atomic % or less.

[0020] Furthermore, the optical device of the present technology uses the above-mentioned conductive laminate as at least one of the electrodes.

[0021] In addition, the method for manufacturing a conductive laminate of the present technology includes the steps of stacking a first transparent material layer, a metal layer containing silver as a main component, and a second transparent material layer in order from the transparent substrate side on at least one surface of a transparent substrate, wherein the first transparent material layer is composed of a composite metal oxide containing at least zinc and tin and containing 10 atomic % or more and 90 atomic % or less of tin, and the second transparent material layer is composed of a metal oxide containing zinc and having a tin content of 10 atomic % or less.

[0022] Effects of the Invention

[0023] According to the present technology, the formation of light-absorbing layers at the interfaces of the conductive laminate can be suppressed, thereby providing a conductive laminate with low resistance and high transmittance for a long period of time. Such a conductive laminate can be used as electrodes for various optical devices such as power-saving, high-performance touch panels, dimming elements, antennas, electrophoretic elements, and light-emitting elements. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] [ Figure 1 ] Figure 1 This is a cross-sectional view schematically showing a configuration example of a conductive laminate to which the present technology is applied.

[0025] [ Figure 2 ] Figure 2 It is a perspective view showing an example of the internal structure of a thin film forming apparatus. DETAILED DESCRIPTION

[0026] Hereinafter, the conductive laminate to which the present technology is applied, the optical device using the conductive laminate, and the method for manufacturing the conductive laminate will be described in detail with reference to the accompanying drawings. It should be noted that the present technology is not limited to the following embodiments, and various modifications can be made without departing from the scope of the present technology. In addition, the accompanying drawings are schematic, and the ratios of various dimensions may sometimes differ from reality. Specific dimensions, etc. should be judged with reference to the following description. In addition, the accompanying drawings naturally also include parts with different dimensional relationships and ratios.

[0027] [Conductive laminate]

[0028] Figure 1 : is a cross-sectional view schematically showing a configuration example of a conductive laminate 1 to which the present technology is applied. Figure 1 As shown, a conductive laminate 1 comprises a first transparent material layer 3, a metal layer 4 containing silver as a main component, and a second transparent material layer 5, which are laminated in this order from the transparent substrate 2 side on at least one surface of a transparent substrate 2. Furthermore, in the conductive laminate 1, the first transparent material layer 3 is composed of a composite metal oxide containing at least zinc and tin, with a tin content of 10 atomic % or more and 90 atomic % or less, and the second transparent material layer 5 is composed of a metal oxide containing zinc and a tin content of 10 atomic % or less.

[0029] When forming each of the layers 3 to 5 of the conductive laminate 1, for example, sputtering, one of the vacuum film-forming techniques, can be used. The present inventors have conducted research by laminating various transparent materials with silver using sputtering. As a result, they have discovered that using a composite oxide containing zinc and tin, with a tin content of 10 atomic % or more and 90 atomic % or less, as the first transparent material layer 3, can suppress light absorption. Furthermore, using a metal oxide containing zinc and having a tin content of 10 atomic % or less as the second transparent material layer 5, can maintain low resistance for a long period of time.

[0030] Here, if zinc oxide is used as the first transparent material layer 3, then a light-absorbing layer is formed when silver is deposited by sputtering after the zinc oxide film is formed. Specifically, silver atoms ejected at high speed from the target lose their kinetic energy upon reaching the transparent substrate 2, becoming fixed to the surface of the transparent substrate 2. At this point, given the strong interaction between the silver atoms ejected at high speed from the target and the metal constituting the first transparent material 3, the silver atoms alloy on the first transparent material layer 3 side, forming a light-absorbing layer. Furthermore, zinc is an element that has a wide solid solution region with the silver constituting the metal layer 4 and strongly interacts with the silver constituting the metal layer 4, thus facilitating the formation of a light-absorbing layer.

[0031] However, as in the present technology, when the first transparent material layer 3 contains tin, in particular, by making the tin content in the first transparent material layer 3 greater than 10 atomic % and less than 90 atomic % relative to the total of zinc and tin, the chemical stability of the composite oxide of zinc and tin can suppress the reaction with silver constituting the metal layer 4 and form a thin film.

[0032] When forming the second transparent material layer 5, if a material with low interaction with the silver constituting the metal layer 4 is used, the second transparent material layer 5 will not fully wet and expand, forming numerous small gaps at the interface, leading to light absorption. Using a metal oxide containing zinc as the second transparent material layer 5 improves surface wettability, enabling a good interface. Furthermore, because zinc strongly bonds with oxygen, it forms an oxide film before alloying with the silver constituting the metal layer 4, effectively suppressing the formation of a light-absorbing layer from the alloy layer. Examples of conductive oxides that can be practically used in the second transparent material layer 5 include zinc oxide and zinc alloy composite oxides. Zinc oxide and zinc alloy composite oxides are preferred because they offer good contact resistance when transferring charge from the outside to the surface of the conductive laminate 1. However, when using a composite oxide of zinc and tin in the second transparent material layer 5, the strong bond can make it difficult to achieve conductivity in a stable phase. To achieve good conductivity, it is often considered to intentionally reduce the oxygen content in the composite oxide from the stoichiometric composition by adjusting the amount of oxygen introduced during sputtering. However, although the composite oxide of zinc and tin can obtain conductivity immediately after film formation, it tends to be oxidized by oxygen in the atmosphere and lose conductivity if kept for a long time.

[0033] Thus, the required properties of the first transparent material layer 3 and the second transparent material layer 5 differ. Specifically, chemical stability is required for the first transparent material layer 3, while electrical conductivity is less important. On the other hand, electrical conductivity is crucial for the second transparent material layer 5. While the addition of tin oxide to zinc oxide improves chemical stability, it also degrades electrical conductivity. Therefore, if the first transparent material layer 3 and the second transparent material layer 5 have the same composition, the effects of the present technology are difficult to achieve.

[0034] In this technology, light absorption at each interface can be suppressed by stacking, in order from the transparent substrate 2 side, a first transparent material layer 3 composed of a composite metal oxide containing at least zinc and tin, with a tin content of 10 atomic % or more and 90 atomic % or less; a metal layer 4 containing silver as a main component; and a second transparent material layer 5 composed of a metal oxide containing zinc and having a tin content of 10 atomic % or less on at least one surface of a transparent substrate 2. This allows for the production of a conductive laminate 1 that exhibits low resistance and high transmittance over a long period of time, even without the use of indium.

[0035] In addition, the conductive laminate 1 according to the present technology can reduce the surface resistance (resistance) and improve the total light transmittance. For example, the surface resistance of the conductive laminate 1 can be less than 20Ω / □, and the total light transmittance can be more than 90%. The measurement method of the surface resistance and the total light transmittance is the same as the measurement method of the embodiment described below. It should be noted that the commonly used ITO (indium tin oxide) film and the like vary depending on the film thickness of the ITO, but most have a surface resistance of 100Ω / □ and a total light transmittance of 88%.

[0036] Therefore, the present technology can be applied to power-saving, high-performance optical devices using at least one conductive laminate 1, such as touch panels, dimming elements, electrophoretic optical elements, light-emitting elements, antennas, etc., which use the conductive laminate as at least one electrode.

[0037] The following describes in detail the layers that make up the conductive laminate 1. As described above, the conductive laminate 1 to which the present technology is applied comprises a first transparent material layer 3, a metal layer 4 primarily composed of silver, and a second transparent material layer 5 stacked in this order, starting from the transparent substrate 2 side, on at least one surface of the transparent substrate 2.

[0038] <Transparent substrate>

[0039] A substrate made of either a glass substrate or a resin film can be used as the transparent substrate 2. When a substrate made of a resin film is used as the transparent substrate 2, it can be manufactured by a roll-to-roll method, thereby improving production efficiency.

[0040] The material of such a resin film is not particularly limited, and for example, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyaramid, polyimide, polycarbonate, polyethylene, polypropylene, triacetylcellulose (TAC), polycycloolefin (COC: Cyclic Olefin Copolymer, COP: Cyclic Olefin Copolymer), etc. can be used.

[0041] The thickness of the transparent substrate 2 is not particularly limited, but is preferably 20 μm or more and 200 μm or less in consideration of ease of handling during production and reduction in thickness of the member when a resin film is used.

[0042] In the conductive laminate 1 , the transparent substrate 2 does not need to have a light transmittance of 100%, and may be transparent within a range where the effects of the present technology are exhibited. For example, the light transmittance is preferably 88% or higher.

[0043] In addition, from the viewpoint of improving the friction resistance of the transparent substrate 2 , thin films made of, for example, acrylic resin may be formed on both surfaces of the transparent substrate 2 by solution coating.

[0044] <First Transparent Material Layer>

[0045] As described above, the first transparent material layer 3 is composed of a composite oxide of zinc and tin, with the ratio of tin being 10 atomic % or more and 90 atomic % or less relative to the total amount of zinc and tin. Furthermore, the first transparent material layer 3 may contain one or more elements other than zinc and tin, within a range not exceeding 50 atomic % relative to the total amount of zinc and tin.

[0046] The thickness of the first transparent material layer 3 is not particularly limited and can be set to a thickness that maximizes transmittance according to the material composition. Specific thickness of the first transparent material layer 3 can be set in the range of 30 to 80 nm.

[0047] The method for forming the first transparent material layer 3 is not particularly limited, but sputtering is preferably used from the viewpoint of improving production efficiency and making the film thickness distribution uniform.

[0048] From the perspective of moisture resistance, etc., the first transparent material layer 3 may be formed in multiple layers. In this case, at least the transparent material layer in contact with the metal layer 4 among the multiple first transparent material layers 3 is composed of a composite metal oxide containing zinc and tin, with the tin content being 10 atomic % or more and 90 atomic % or less.

[0049] <Metal Layer>

[0050] The metal layer 4 stacked on the first transparent material layer 3 is a metal layer composed primarily of silver. The metal layer 4 may contain at least 90 atomic percent silver and may contain additive elements up to 10 atomic percent of the total. In other words, the metal layer 4 may be composed of at least 90 atomic percent silver or pure silver.

[0051] The thickness of the metal layer 4 is preferably 5 nm or greater. By setting the thickness of the metal layer 4 to 5 nm or greater, it is easier to form a continuous film and can also suppress absorption caused by the islanding of the silver constituting the metal layer 4. In other words, if the thickness of the metal layer 4 is thinner than 5 nm, island-like films are more likely to form, potentially hindering light transmittance. The upper limit of the thickness of the metal layer 4 is not particularly limited, but is preferably less than 15 nm. By setting the thickness of the metal layer 4 to less than 15 nm, it is possible to more effectively suppress light absorption within the silver layer constituting the metal layer 4 from being greater than absorption at the interface.

[0052] The method for forming the metal layer 4 is not particularly limited. It is preferred to form the second transparent material layer 5 continuously after forming the metal layer 4. From the viewpoint of improving production efficiency and making the film thickness distribution uniform, sputtering is preferably used.

[0053] <Second Transparent Material Layer>

[0054] As described above, the second transparent material layer 5 stacked on the metal layer 4 is composed of a metal oxide containing zinc and having a tin content of 10 atomic % or less. In particular, from the perspective of further enhancing the effectiveness of the present technology, the tin content in the second transparent material layer 5 is preferably less than the tin content in the first transparent material layer 3. The lower limit of the tin content in the second transparent material layer 5 is not particularly limited and can be 0 atomic %, 1 atomic % or greater, 4 atomic % or greater, 6 atomic % or greater, or 8 atomic % or greater.

[0055] From the perspectives of optical properties, conductivity, and chemical stability, the second transparent material layer 5 may contain one or more elements other than zinc, within a range not exceeding 50 atomic percent. In particular, the second transparent material layer 5 preferably contains at least 2 atomic percent of at least one of aluminum and gallium, and more preferably at least 2 atomic percent of either aluminum or gallium. This further improves the conductivity of the second transparent material layer 5. When the second transparent material layer 5 contains at least one of aluminum and gallium, the upper limit of the combined amount of aluminum and gallium is not particularly limited and may be, for example, 15 atomic percent or less, 12 atomic percent or less, 10 atomic percent or less, 8 atomic percent or less, or 5 atomic percent or less.

[0056] The thickness of the second transparent material layer 5 is not particularly limited and can be set to a thickness that maximizes transmittance according to the material composition. Specific thickness of the second transparent material layer 5 can be, for example, in the range of 30 to 70 nm.

[0057] The method for forming the second transparent material layer 5 is not particularly limited, but is preferably formed continuously after the metal layer 4 is formed. From the viewpoint of improving production efficiency and making the film thickness distribution uniform, sputtering is preferably used.

[0058] From the perspective of scratch resistance, the second transparent material layer 5 can be formed in multiple layers. In this case, at least the transparent material layer in contact with the metal layer 4 among the multiple second transparent material layers 5 is composed of a metal oxide containing zinc and having a tin content of 10 atomic % or less, and may contain one or more elements within a range not exceeding 50 atomic %. Furthermore, in order to maintain good electrical conductivity, the other layers of the multiple second transparent material layers 5 other than the transparent material layer in contact with the metal layer 4 are preferably conductive transparent oxides.

[0059] It should be noted that Figure 1 The conductive laminate 1 shown has a first transparent material layer 3, a metal layer 4 and a second transparent material layer 5 stacked on one side of a transparent substrate 2, but the first transparent material layer 3, the metal layer 4 and the second transparent material layer 5 may also be stacked on the other side of the transparent substrate 2 or on both sides of the transparent substrate 2.

[0060] [Method for producing a conductive laminate]

[0061] The conductive laminate 1 can be produced by laminating the first transparent material layer 3 , the metal layer 4 containing silver as a main component, and the second transparent material layer 5 in this order from the transparent substrate 2 side on at least one surface of the transparent substrate 2 .

[0062] The first transparent material layer 3 , the metal layer 4 , and the second transparent material layer 5 can be formed using, for example, a thin film forming apparatus described in Japanese Patent Application Laid-Open No. 2014-34701. Figure 2 This is a perspective view showing the internal structure of a thin film forming apparatus described in Japanese Patent Application Laid-Open No. 2014-34701. This thin film forming apparatus forms films on a film substrate by sputtering using a roll-to-roll method. Multiple sputtering targets can be installed, and once the rolls are installed, films of various materials can be formed while maintaining a vacuum atmosphere.

[0063] Furthermore, in this thin film forming apparatus, oxygen gas can be introduced into the plasma in addition to argon gas as a sputtering gas during sputtering, thereby enabling formation of an oxide of the target material on the film substrate.

[0064] The following describes the structure of a thin film forming apparatus in detail. This apparatus comprises a measuring unit, a supply unit, and a control unit, and is capable of forming a thin film with uniform thickness in both the longitudinal and width directions. The measuring unit continuously supplies a substrate film in the longitudinal direction and measures the optical properties of the thin film formed thereon in the width direction. The supply unit is equipped with multiple gas nozzles across the width of the substrate film to supply reactive gas near a target. The control unit controls the flow rate of the reactive gas ejected from each gas nozzle based on the optical properties of the measuring unit in the width direction.

[0065] Furthermore, as a specific configuration, it is preferable to include a film-forming unit comprising a supply unit, sputtering electrodes for applying voltage to targets, and a plasma measurement unit for measuring the emission spectrum of plasma across the width of the substrate film being formed. This allows the control unit to control the flow rate of reactive gas ejected from each gas nozzle and the voltage applied to the target based on the optical characteristics of the measurement unit across the width and the emission spectrum of the plasma measurement unit, thereby enabling the formation of a thin film with a more uniform thickness across the width.

[0066] Furthermore, as a specific structure, it is preferred to include an unwinding section for unwinding the substrate film in the longitudinal direction, a film-forming unit having multiple film-forming sections arranged along the longitudinal direction of the substrate film, and a take-up section for taking up the substrate film formed in the film-forming unit. This allows for the formation of multi-layer thin films from the unwinding to the take-up of the substrate film. Furthermore, the measuring section is preferably positioned after each film-forming section, but preferably at least after the last film-forming section, i.e., between the film-forming unit and the take-up section. This allows for the measurement of the optical properties of both single-layer thin films and multi-layer thin films.

[0067] Figure 2 The thin film forming apparatus shown moves a base film as a substrate film while being wound around a can roll, and forms a thin film on the surface of the base film by sputtering.

[0068] This thin film forming apparatus supplies a base film 10 (transparent substrate 2) from a delivery roll 11, which serves as a delivery unit, and takes up the thin film-formed base film 10 using a take-up roll 12, which serves as a take-up unit. Furthermore, a first film forming chamber unit and a second film forming chamber unit are provided within a vacuum chamber. The vacuum chamber is connected to a vacuum pump for exhausting air, allowing it to be adjusted to a predetermined vacuum level.

[0069] The first and second film-forming chamber units are each equipped with a first can roll 21 and a second can roll 22. Multiple sputtering chambers SP1 to 10, serving as film-forming sections, are arranged so as to face the outer circumferences of the can rolls 21 and 22. Each of the sputtering chambers SP1 to 10 has a predetermined target mounted on an electrode, and a supply unit having multiple gas nozzles is provided across the width of the base film 10.

[0070] The thin film forming apparatus also includes an optical monitor 31, a measuring unit, for measuring optical characteristics between the first and second film forming chamber units (i.e., after film formation in sputtering chamber SP5). This allows for control of film formation of intermediate products after the first film forming chamber unit and reduces adjustment time for single-layer adjustments. Furthermore, an optical monitor 32, a measuring unit, for measuring optical characteristics after the second film forming chamber unit (i.e., after film formation in sputtering chamber SP10), is included. This allows for confirmation of the film quality of the final product after the second film forming chamber unit.

[0071] As described later, the optical monitors 31 and 32 use an optical head capable of scanning in the width direction to measure the optical characteristics of the thin film formed on the base film 10 in the width direction. By measuring the peak wavelength of the reflectivity as an optical characteristic using the optical monitors 31 and 32 and converting it into an optical thickness, the optical thickness distribution in the width direction can be obtained.

[0072] The thin film forming apparatus having such a structure unwinds a base film 10 from a delivery roll 11, forms a thin film on the base film 10 while being conveyed by a first can roll 21 and a second can roll 22, and then winds it up on a take-up roll 12, thereby producing a multilayer film. The optical characteristics of the thin film formed on the base film 10 in the width direction are measured by optical monitors 31 and 32. Based on these optical characteristics, the flow rate of reactive gas from each gas nozzle arranged in the width direction is controlled, thereby forming a film of uniform thickness in both the longitudinal and width directions.

[0073] Example

[0074] Hereinafter, the present technology will be described in detail with reference to Examples and Comparative Examples, but the present technology is not limited to the following Examples.

[0075] <Example 1>

[0076] use Figure 2 The thin film forming apparatus described in Japanese Patent Application Laid-Open No. 2014-34701 sequentially forms a first transparent material layer, a metal layer, and a second transparent material layer on a transparent substrate. A 50 μm thick COP film is used as the transparent substrate.

[0077] The thin-film forming apparatus is capable of simultaneously and sequentially laminating thin films made of multiple materials. In this example, targets consisting of zinc oxide containing 50 atomic percent tin (hereinafter referred to as "50 atm% Sn-Zn-O"), silver, and zinc oxide are positioned in order, starting from the film unwinding side. Each target is connected to an independent power source, enabling discharge at any power source. Furthermore, each target is housed in a separate container, with the partition walls separating the targets having only a slight gap near the can roll, enabling the creation of substantially different gas atmospheres.

[0078] The entire vacuum chamber of the thin film forming apparatus was evacuated to a vacuum of 1×10 -3 After the pressure drops below Pa, argon gas is introduced into the first cathode section of the vacuum chamber, where 50 atm% Sn-Zn-O is located, at a flow rate of 150 sccm, adjusted using a mass flow controller. Electricity is applied to the 50 atm% Sn-Zn-O target to discharge it, and film formation by sputtering is performed. To suppress light absorption by the 50 atm% Sn-Zn-O due to oxygen deficiency, 6 sccm of oxygen is added to form a transparent oxide layer. The film is moved at a speed of 3 m / min. The power is adjusted to achieve a 64 nm thickness of 50 atm% Sn-Zn-O at a speed of 3 m / min, after previously measuring the relationship between power and film thickness.

[0079] After forming 50atm% Sn-Zn-O in the first cathode part, a silver thin film is formed in the second cathode part. Specifically, in the second cathode part, argon gas is introduced into the second cathode part of the vacuum tank while being adjusted by a mass flow controller to a flow rate of 450sccm, and power is applied to the silver target to discharge it, thereby performing film formation based on sputtering. In this embodiment, two adjacent cathodes are used, but it is not necessarily necessary to use two adjacent cathodes. Depending on the device structure, it is also possible to use the entire cathode chamber as a partition wall instead of one cathode chamber. The power is adjusted so that a silver thin film with a thickness of 7nm can be formed at a moving speed of 3m / min after the relationship between the power and the film thickness is measured in advance.

[0080] After the silver thin film is formed in the second cathode portion, zinc oxide is formed in the third cathode portion. Specifically, in the third cathode portion, argon gas is introduced into the third cathode portion of the vacuum tank while being adjusted to a flow rate of 150 sccm by a mass flow controller, and power is applied to the zinc oxide target to discharge it, and film formation based on sputtering is performed. At this time, separately from the argon gas, a trace amount of oxygen is introduced while being adjusted by a mass flow controller, and the amount of oxygen is adjusted in a manner that does not cause poor conductivity due to insufficient or excessive oxygen, thereby obtaining a good transparent conductive oxide. In this embodiment, two adjacent cathodes are used, but it is not necessarily necessary to use two adjacent cathodes. Depending on the device structure, it is also possible not to use one cathode chamber, and the entire cathode chamber can be used as a partition. The power is adjusted so that zinc oxide with a thickness of 46 nm can be formed at a moving speed of 3 m / min after the relationship between the power and the film thickness is measured in advance.

[0081] After forming 3 layers of film, the film is continuously wound up to form Figure 1 After forming a film with the structure of the device, the atmosphere is introduced into the entire device and the sample is taken out as a sample.

[0082] <Example 2>

[0083] A sample was prepared under the same conditions as in Example 1 except that the target provided at the third cathode portion was changed from zinc oxide to zinc oxide containing 10 atomic % tin and the discharge conditions were adjusted so as to obtain the same film formation rate as that of zinc oxide.

[0084] <Example 3>

[0085] A sample was prepared under the same conditions as in Example 1 except that the target provided at the first cathode portion was changed from zinc oxide containing 50 atomic % tin to zinc oxide containing 10 atomic % tin and the discharge conditions were adjusted so as to obtain the same film formation rate as that of zinc oxide containing 50 atomic % tin.

[0086] <Example 4>

[0087] The target set in the first cathode part was changed from zinc oxide containing 50 atomic % tin to zinc oxide containing 90 atomic % tin, and the discharge conditions were adjusted so that the film thickness became 55 nm. In addition, the discharge conditions were adjusted so that the film thickness of zinc oxide formed in the third cathode part became 51 nm. Otherwise, the sample was prepared under the same conditions as in Example 1.

[0088] <Example 5>

[0089] The discharge conditions were adjusted so that the film thickness of zinc oxide containing 50 atomic % tin formed on the first cathode portion was 63 nm. In addition, the target set at the third cathode portion was changed from zinc oxide to zinc oxide containing 5 atomic % aluminum, and the discharge conditions were adjusted so that the film thickness was 46 nm. Other than this, the sample was prepared under the same conditions as in Example 1.

[0090] <Example 6>

[0091] The discharge conditions were adjusted so that the film thickness of zinc oxide containing 50 atomic % tin formed in the first cathode portion was 63 nm. In addition, the target set in the third cathode portion was changed from zinc oxide to zinc oxide containing 10 atomic % gallium, and the discharge conditions were adjusted so that the film thickness was 43 nm. Except for this, the sample was prepared under the same conditions as in Example 1.

[0092] <Comparative Example 1>

[0093] A sample was prepared under the same conditions as in Example 1 except that the target provided in the third cathode portion was changed from zinc oxide to zinc oxide containing 15 atomic % of tin and the discharge conditions were adjusted so as to obtain the same film formation rate as that of zinc oxide.

[0094] <Comparative Example 2>

[0095] The discharge conditions were adjusted so that the film thickness of zinc oxide containing 50 atomic % tin formed on the first cathode portion was 65 nm. In addition, the target set at the third cathode portion was changed from zinc oxide to zinc oxide containing 50 atomic % tin, and the discharge conditions were adjusted so that the film thickness was 47 nm. Except for this, the sample was prepared under the same conditions as in Example 1.

[0096] <Comparative Example 3>

[0097] A sample was prepared under the same conditions as in Example 1, except that the target provided in the first cathode portion was changed from zinc oxide containing 50 atomic % of tin to zinc oxide.

[0098] <Comparative Example 4>

[0099] The target set at the first cathode part was changed from zinc oxide containing 50 atomic % tin to tin oxide, and the discharge conditions were adjusted so that the film thickness was 47 nm. In addition, the discharge conditions were adjusted so that the film thickness of zinc oxide formed at the third cathode part was 56 nm. Except for this, the sample was prepared under the same conditions as in Example 1.

[0100] <Comparative Example 5>

[0101] A sample was prepared under the same conditions as in Example 1, except that the target provided in the first cathode portion was changed from zinc oxide containing 50 atomic % of tin to zinc oxide containing 5 atomic % of tin.

[0102] <Comparative Example 6>

[0103] The target set in the first cathode part was changed from zinc oxide containing 50 atomic % tin to zinc oxide containing 95 atomic % tin, and the discharge conditions were adjusted so that the film thickness was 52 nm. In addition, the discharge conditions were adjusted so that the film thickness of zinc oxide formed in the third cathode part was 51 nm. Except for this, the sample was prepared under the same conditions as in Example 1.

[0104] [Evaluation results]

[0105] Each sample was cut into an arbitrary size and then measured and evaluated.

[0106] <Surface resistance>

[0107] Surface resistance was measured in accordance with JIS K-7194 using a contact resistance meter, the Loresta GP (registered trademark) (manufactured by DIA INSTRUMENTS Co., Ltd.). Specifically, to evaluate the long-term stability of each sample, the initial resistance value and the resistance value after 240 hours of exposure to an environment at 65°C and 90% relative humidity were measured. At this point, values ​​below 20 Ω / □, which is not an indicator of surface resistance, were considered unsuitable for practical use. The results are shown in Table 1.

[0108] <Total light transmittance>

[0109] The total light transmittance was measured using "NDH5000 (manufactured by Nippon Denshoku Industries, Ltd.)" in accordance with "JIS K-7105".

[0110] <Light Absorption>

[0111] Light absorption: The transmittance and reflectance at an incident angle of 5° were measured using a spectrometer "U-4100 (manufactured by Hitachi High-Technologies Corporation)". The amount expressed by the following formula (1) for each value at a wavelength of 550 nm was defined as the light absorption amount.

[0112] Light absorption (%) = 100 (%) - (transmittance (%) + reflectance (%)) ... (1)

[0113] That is, light that is neither reflected nor transmitted is converted (absorbed) into heat within the film and substrate. In reality, scattering and other factors can sometimes reduce the actual transmittance and reflectance, resulting in an apparent increase in light absorption. However, the substrate used in the present invention has minimal absorption and a smooth surface. Therefore, the light absorption calculated using equation (1) can be roughly considered to be absorption caused by the laminated film. The results are shown in Table 1.

[0114] [Table 1]

[0115]

[0116] <Example 1>

[0117] The sample of Example 1 maintained a surface resistance of less than 20Ω / □ and a total light transmittance of more than 90%. In addition, no significant change in resistance was observed even in a high temperature and high humidity environment, indicating that it can withstand long-term use.

[0118] <Example 2>

[0119] Although the sample of Example 2, in which 10 atomic % tin is added to the second transparent material of Example 1, has a higher resistance value than the sample of Example 1 when placed in a high temperature and high humidity environment, it maintains a surface resistance of less than 20Ω / □ and a total light transmittance of more than 90%, indicating that it can withstand long-term use.

[0120] <Examples 3 and 4>

[0121] The samples of Examples 3 and 4, in which the tin concentration of the first transparent material in Example 1 is changed to 10 atomic % or 90 atomic %, have increased light absorption at a wavelength of 550 nm compared to the sample of Example 1. When placed in a high temperature and high humidity environment, although the resistance value increases, the surface resistance is maintained below 20Ω / □ and the total light transmittance is maintained above 90%, indicating that it can withstand long-term use.

[0122] <Examples 5 and 6>

[0123] Samples in Examples 5 and 6, which incorporate aluminum or gallium into the second transparent material of Example 1, maintain a surface resistance below 20Ω / □ and a total light transmittance of over 90%. Furthermore, even in high-temperature and high-humidity environments, the resistance value does not change significantly, demonstrating its ability to withstand long-term use. It should be noted that the resistance values ​​of samples in Examples 5 and 6 are slightly lower than those of the sample in Example 1. This is believed to be due to the increased conductivity of the second transparent material caused by the addition of aluminum or gallium.

[0124] Comparative Examples 1 and 2

[0125] In the samples of Comparative Examples 1 and 2 in which 15 atomic % or 50 atomic % tin was added to the second transparent material of Example 1, the initial resistance values ​​all met the indicators, but the resistance values ​​increased significantly under high temperature and high humidity environments. It should be noted that for the samples of Comparative Examples 1 and 2, the surface resistance was measured using other non-contact resistivity meters instead of the above-mentioned contact resistance measuring instrument. The results show that even under high temperature and high humidity environments, the resistance values ​​showed almost no change from the initial ones. The reason is as follows. In the structure of the present technology, the current flows in the metal layer via the second transparent material layer on the surface in contact with the measuring terminal, and returns to the measuring terminal via the second transparent material layer and is measured. It is believed that the resistance value is roughly determined by the value in the metal layer. Although it is only less than 100 nm, the second transparent material layer is oxidized under high temperature and high humidity environments, and the insulation becomes extremely high. Therefore, it is presumed that it cannot be measured using a contact resistivity meter.

[0126] <Comparative Examples 3 to 6>

[0127] In samples from Comparative Examples 3 to 6, which varied the tin content of the first transparent material in Example 1, the resistance remained stable even under high-temperature and high-humidity conditions, but the total light transmittance decreased significantly. This is believed to be due to the tin content of the first transparent material layer not being between 10 atomic % and 90 atomic %, resulting in increased light absorption and a corresponding decrease in transmittance. Furthermore, as mentioned above, this light absorption is presumed to be caused by the formation of an absorption layer between the first transparent material layer and the metal layer (silver).

[0128] As described above, the effects of the present technology have been confirmed from the results of the examples and comparative examples. It should be noted that the present technology is not limited to the examples described above, and it is obvious that a person with ordinary knowledge in the field of the present technology can conceive of various changes or modifications within the scope of the technical concept described in the claims.

[0129] Explanation of symbols

[0130] 1: Conductive laminate, 2: Transparent substrate, 3: First transparent material layer, 4: Metal layer, 5: Second transparent material layer, 10: Base film, 11: Unwinding roller, 12: Winding roller, 21: First can roller, 22: Second can roller, 31: Optical monitor, 32: Optical monitor, SP: Sputtering chamber.

Claims

1. A conductive laminate, wherein a first transparent material layer, a metal layer containing silver as a main component, and a second transparent material layer are laminated in this order from the transparent substrate side on at least one surface of a transparent substrate, The first transparent material layer is composed of a composite metal oxide containing at least zinc and tin and containing 10 atomic % or more and 90 atomic % or less of tin, The second transparent material layer is composed of a metal oxide containing zinc and having a tin content of 10 atomic % or less. The first transparent material layer and the second transparent material layer have different compositions.

2. The conductive laminate according to claim 1, wherein The second transparent material layer contains 2 atomic % or more of at least one of aluminum and gallium.

3. The conductive laminate according to claim 1 or 2, wherein The metal layer contains 90 atomic % or more of silver.

4. The conductive laminate according to claim 1 or 2, wherein The thickness of the metal layer is greater than 5 nm.

5. The conductive laminate according to claim 1 or 2, wherein The transparent substrate is made of any one of glass, polyethylene terephthalate PET, polyethylene naphthalate PEN, polyaramide, polyimide, polycarbonate, polyethylene, polypropylene, triacetyl cellulose TAC, polycycloolefin (COC), and COP, or a laminate thereof.

6. The conductive laminate according to claim 1 or 2, wherein The content rate of tin in the second transparent material layer is lower than the content rate of tin in the first transparent material layer. 7 . A touch panel using the conductive laminate according to claim 1 as at least one electrode. 8 . A light control element using the conductive laminate according to claim 1 as at least one of electrodes. 9 . An electrophoretic optical element using the conductive laminate according to claim 1 as at least one of electrodes. 10 . A light emitting element using the conductive laminate according to claim 1 as at least one electrode. 11 . An antenna comprising at least one conductive laminate according to claim 1 .

12. A method for producing a conductive laminate, comprising the steps of laminating a first transparent material layer, a metal layer containing silver as a main component, and a second transparent material layer in order from the transparent substrate side on at least one surface of a transparent substrate, The first transparent material layer is composed of a composite metal oxide containing at least zinc and tin and containing 10 atomic % or more and 90 atomic % or less of tin, The second transparent material layer is composed of a metal oxide containing zinc and having a tin content of 10 atomic % or less. The first transparent material layer and the second transparent material layer have different compositions.

Citation Information

Patent Citations

  • Thin film deposition device and thin film deposition method

    JP2014034701A

  • laminate

    CA2179853A1

  • TFT substrate and production method therefor, and transparent conductive film laminate substrate provided with al wiring and production method therefor, and transparent conductive film laminate circui

    CN101099188A

  • Sputtering target

    CN101880859A

  • Conductive laminate, transparent conductive laminate with patterned wiring, and optical device

    CN103608872A